Fluctuations in range and abundance of snow crab (Chionoecetes opilio) from the eastern Bering Sea: What role for Pacific cod (Gadus macrocephalus) predation? - Burgos, Julian; Ernst, Billy; Armstrong, David; Orensanz, Jose Maria (Bulletin of Marine Science)
Fluctuations in abundance of commercially valuable crustacean stocks in sub-Arctic ecosystems have been variously attributed to the effects of climatic forcing, fishing pressure, and predation, mostly by gadoid fishes. Landings of snow crab, Chionoecetes opilio (J. C. Fabricius, 1788), from the eastern Bering Sea declined after the early 1990s, reaching historical lows a decade later. At the same time, two phenomena became apparent in the dynamics of the primiparae (first-time female breeders): their geographic range contracted to the northwest along the middle shelf (50–100 m depth), and the contraction was punctuated by periodic recruitment to the mature female pool, with a period of approximately 7 yrs and declining amplitude. The first phenomenon has been addressed by the environmental ratchet hypothesis, which attributes the contraction to a combination of an ontogenetic female migration, circulation patterns, the spatial dynamics of benthic stages in relation to near-bottom temperature, and predation by Pacific cod, Gadus macrocephalus Tilesius, 1810. Mortality due to cod predation in the Middle Domain, apparently related to near-bottom temperature, increased after 1995, contributing to the ratchet effect and the disappearance of periodic pulses of primipara abundance. Cod predation does not, however, appear to have controlled the frequency of periodic recruitment fluctuations. On the other hand, amplitude of fluctuations of primipara abundance in the Middle Domain, purportedly the "engine" of renewal of this stock, do appear to be affected by both predation and climate, whose interaction is complex but perhaps interpretable. Fil: Burgos, Julian. Marine Research Institute; Islandia Fil: Ernst, Billy. Universidad de Concepción; Chile Fil: Armstrong, David. University of Washington; Estados Unidos Fil: Orensanz, Jose Maria. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Nacional Patagónico; Argentina